Peningkatan Pemahaman Masyarakat Terhadap Ibadah Dengan Menerapkan Kajian Fiqh Ibadah Pada Masyarakat Nagari Sungai Durian - Syaibatul Insani; Sriwahyuni Sriwahyuni; Rifza Irmada Yanti; Dezi Zakiyatul Insani; Gina Zayes Putri; Nadjmudin Nadjmudin; Muhammad Yasir; Hasbi Kurnia putra; Sabri Wassalam; Reyhan Ramadana; Edriagus Saputra; Nora Afnita (Universitas Sumatera Barat, 2024)
The study of fiqh is indeed a very important material. Because it is related to how Islamic law is carried out. Especially those related to mahdhah worship, therefore every Muslim man and woman must learn to understand it so that in its implementation it can run well in accordance with religious orders. This community service activity was carried out on the congregation of the Jambak Kalawi Korong Sungai Durian Surau related to strengthening and mentoring the fiqh of worship. The result of this activity was the increase in the insight of the congregation of the Jambak Kalawi Surau regarding istinja', obligatory bathing, breaking ablution, menstruation, and postpartum. The enthusiasm of the congregation also showed a positive attitude, so that this activity ran smoothly.